Leisure Patterns and Values in Adolescents from Serbia born in 1990s: An Attempt at Building a Bridge between the Two Domains - Ivana Stepanović Ilić; Marina Videnović; Nebojša Petrović (Srpska Politička Misao)
This work is an attempt at empirically establishing a relation between leisure and values in adolescents. Being new, this topic could help a broader understanding of youth leisure and its association with inner psychological dispositions, but also with specific social context (prolonged economic crisis and post-war environment). Five typical leisure patterns were previously identified: academic, sports, going out, following celebrities in the media and music, and computers pattern. The main objective was to discover whether students with high and low scores on these patterns differ regarding their values. The sample consisted of 2426 Serbian secondary school students from 9 towns. A discriminant analysis was performed and showed that it was possible to identify a specific mix of personal and social values for every leisure pattern. This confirms the existence of a relation between students’ behaviour during free time and their values, expressed as a preference for specific personal and social goals. The resultss imply that connecting two domains is achievable and fruitful in both ways. The identified leisure patterns contribute to a more detailed and elaborate portrayal of adolescents’ values but those values also bring a new insight into specific features of adolescents’ behaviour during leisure time.